Negotiating rankings and mobility: A comparative analysis of metric adaptation across four flagship universities - Hassan, Sinaria (Journal of International Students, 2026)
Global university rankings have evolved from informational tools into governing frameworks that shape institutional strategy and international student mobility, often reinforcing systemic inequities and epistemic. This study examines how four flagship universities — Tsinghua University (China), Jagiellonian University (Poland), Universidade Estadual Paulista (Brazil), and the University of Wisconsin-Madison (USA) — navigate ranking pressures while leveraging artificial intelligence to recalibrate mobility patterns. Using a comparative case design informed by Qualitative Comparative Analysis, the study integrates ranking data, policy documents, forty-five interviews, and digital engagement metrics spanning 2020–2025. Findings reveal four persistent tensions: prestige versus equity, cultural identity versus algorithmic homogenization, infrastructural constraints versus innovation, and regulatory sovereignty versus global integration. The analysis is theoretically anchored in contextual integrity, relational mobility, and pluriversal validation. Results indicate that metric adaptation is a negotiated political process in which elite institutions leverage rankings for global visibility while managing competing local imperatives. The study advocates for equity-oriented metrics, digital sovereignty investments, and participatory algorithmic governance as pathways toward inclusive and sustainable international student mobility.